Wave energy assessment and wave converter applicability at the Pacific coast of Central America - Corrales-Gonzalez, Manuel; Lavidas, George; Lira-Loarca, Andrea; Besio, Giovanni (Frontiers in Energy Research, 2024)
Nowadays, numerous governments have instituted diverse regulatory frameworks aimed at fostering the assimilation of sustainable energy sources characterized by reduced environmental footprints. Solar, wind, geothermal, and ocean energies were subject to extensive scrutiny, owing to their ecological merits. However, these sources exhibit pronounced temporal fluctuations. Notably, ocean dynamics offer vast energy reservoirs, wherein oceanic waves contain relevant energy amount. In the Central American Pacific context, the exploration of wave energy resources is currently underway. Accurate numerical wave models are required for applied studies such as those oriented to the estimation of exploitable wave power, and even more so in the Central American region of the Pacific Ocean where existing numerical models simulations have so far relied on coarse resolution and limited validation field data. This work presents a high resolution unstructured wave hindcast over the Central American Pacific region, implemented by means of the third-generation spectral wave model WavewatchIII over the period comprised between 1979 and 2021. Results of the significant wave height have been bias-corrected on the basis of satellite information spanning 2005 to 2015, and further validation was done by using wave buoy and Acoustic Doppler Current Profiler records located in the nearshore region of the Central America Pacific coast. After correction and validation of the wave hindcast, we employed the dataset for the evaluation and assessment of wave energy and its possible exploitation by means of different wave energy converters. This evaluation addressed the imperative of diversifying the energy portfolio within the Exclusive Economic Zones of Guatemala,